2018
DOI: 10.1007/s00421-018-3806-2
|View full text |Cite
|
Sign up to set email alerts
|

Lower body blood flow restriction training may induce remote muscle strength adaptations in an active unrestricted arm

Abstract: Lower limb BFR training increased trained arm strength more than the contralateral untrained arm, and the trained arm of controls. However, there was no additional effect on muscle CSA. These findings support evidence for a BFR training-derived remote strength transfer that may be relevant to populations with localised movement disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 44 publications
3
46
0
Order By: Relevance
“…The only previous meta-analysis performed on LL-BFR training versus HLT in healthy adults 25 included studies that had within-subject controls and/or used non-randomized allocation procedures, while also including more than one strength outcome variable from the same populations. Cross-transfer effects have been reported for contralateral limb following LL-BFR training 26,27 ; thus, inclusion of studies involving within-subject designs may not reflect the direct effects of LL-BFR training. Furthermore, non-randomized designs may involve selection bias, while inclusion of the same study population multiple times in the quantitative meta-analysis (double counting) inherently will increase the statistical weighting of that study population.…”
mentioning
confidence: 99%
“…The only previous meta-analysis performed on LL-BFR training versus HLT in healthy adults 25 included studies that had within-subject controls and/or used non-randomized allocation procedures, while also including more than one strength outcome variable from the same populations. Cross-transfer effects have been reported for contralateral limb following LL-BFR training 26,27 ; thus, inclusion of studies involving within-subject designs may not reflect the direct effects of LL-BFR training. Furthermore, non-randomized designs may involve selection bias, while inclusion of the same study population multiple times in the quantitative meta-analysis (double counting) inherently will increase the statistical weighting of that study population.…”
mentioning
confidence: 99%
“…The populations examined were relatively heterogeneous between studies, with the most common population being healthy non‐resistance trained but recreationally active adults, examined in 23 of the 52 included studies 17,24,31‐51 . Other populations included resistance‐trained adults, adults with musculoskeletal or soft tissue injuries, older adults, or adults with hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…Other populations included resistance‐trained adults, adults with musculoskeletal or soft tissue injuries, older adults, or adults with hypertension. There were far more studies (26 of 52) examining only male participants, 17,24,25,30,32‐38,41‐43,46,48,50‐59 compared with just 8 of 52 examining only female participants, 40,49,60‐65 leaving 18 studies examining both of these genders 8,19,20,39,44,45,47,66‐75 …”
Section: Resultsmentioning
confidence: 99%
“…20 Newer research is demonstrating that the effects of BFR therapy may be more closely linked to systemically driven hormonal and cellular changes than originally thought. 52,53 For example, demonstrable differences in strength in the upper extremity were only notable when a cross transfer effect was induced by using BFR concurrently in the lower extremity, activating larger muscle groups and eliciting a larger systemic response. 52,53 As mentioned previously, BFR has been shown to increase sympathetic nervous system activity, which may help to explain the observed effect on pain with activity.…”
Section: Discussionmentioning
confidence: 99%
“…52,53 For example, demonstrable differences in strength in the upper extremity were only notable when a cross transfer effect was induced by using BFR concurrently in the lower extremity, activating larger muscle groups and eliciting a larger systemic response. 52,53 As mentioned previously, BFR has been shown to increase sympathetic nervous system activity, which may help to explain the observed effect on pain with activity. [39][40][41][42][43] St. John et al found that patients presenting to an upper extremity clinic who had better pain scores also had better physical function when compared with patients with worse pain scores.…”
Section: Discussionmentioning
confidence: 99%